Insurance status and disparities in disease presentation, treatment, and outcomes for men with germ cell tumors. Issue 20 (8th August 2016) - Markt, Sarah C.; Lago‐Hernandez, Carlos A.; Miller, Rowan E.; Mahal, Brandon A.; Bernard, Brandon; Albiges, Laurence; Frazier, Lindsay A.; Beard, Clair J.; Wright, Alexi A.; Sweeney, Christopher J.
Abstract : BACKGROUND: People aged 26 to 34 years represent the greatest proportion of the uninsured, and they have the highest incidence of testicular cancers. The aim of this study was to investigate the association between insurance status and cancer outcomes in men diagnosed with germ cell tumors. METHODS: The Surveillance, Epidemiology, and End Results database was used to identify 10, 211 men diagnosed with germ cell gonadal neoplasms from 2007 to 2011. Associations between insurance status and characteristics at diagnosis and receipt of treatment were examined with log‐binomial regression. The association between insurance status and mortality was assessed with Cox proportional hazards regression. RESULTS: Uninsured patients had an increased risk of metastatic disease at diagnosis (relative risk [RR], 1.26; 95% confidence interval [CI], 1.15‐1.38) in comparison with insured patients, as did Medicaid patients (RR, 1.62; 95% CI, 1.51‐1.74). Among men with metastatic disease, uninsured and Medicaid patients were more likely to be diagnosed with intermediate/poor‐risk disease (RR for uninsured patients, 1.22; 95% CI, 1.04‐1.44; RR for Medicaid patients, 1.39; 95% CI, 1.23‐1.57) and were less likely to undergo lymph node dissection (RR for uninsured patients, 0.74; 95% CI, 0.57‐0.94; RR for Medicaid patients, 0.76; 95% CI, 0.63‐0.92) in comparison with insured patients. Men without insurance were more likely to die of their disease (hazard ratio [HR], 1.88; 95% CI, 1.29‐2.75) in comparison with insured men, as were those with Medicaid (HR, 1.51; 95% CI, 1.08‐2.10). CONCLUSIONS: Patients without insurance and patients with Medicaid have an increased risk of presenting with advanced disease and dying of the disease in comparison with those who have insurance. Future studies should examine whether implementation of the Patient Protection and Affordable Care Act reduces these disparities. Cancer 2016;122:3127–35 . © 2016 American Cancer Society . Abstract : Patients without insurance and patients with Medicaid have an increased risk of presenting with advanced disease and dying from the disease in comparison with those who have insurance. Future studies should examine whether the implementation of the Patient Protection and Affordable Care Act reduces these disparities. See also pages 3106‐9 and 3157‐65.